Clinical and Kinematic Correlates of Favorable Gait Outcomes From Subthalamic Stimulation - Cebi, Idil; Scholten, Marlieke; Gharabaghi, Alireza; Weiss, Daniel (Frontiers in Neurology, 2020)
Objective: Gait and freezing of gait (FoG) are highly relevant to the outcomes of subthalamic deep brain stimulation (STN-DBS) in Parkinson’s disease (PD). Previous studies pointed to variable response to combined dopaminergic and STN-DBS treatment. Here, we performed a prospective exploratory study on associations of preoperative clinical and kinematic gait measures with quantitative gait and FoG outcomes after STN-DBS implantation. Methods: We characterized 18 consecutive PD patients (13 freezers) before and after STN-DBS implantation. The patients received preoperative levodopa challenges (MedOff vs MedOn) and a postoperative reassessment at six months from surgery in MedOn/StimOn condition. We correlated the FoG outcome, calculated as improvement of Freezing of Gait Assessment Course (FoG-AC) from baseline MedOff to six months follow-up MedOn/StimOn, with the levodopa response of preoperative clinical and kinematic gait measures. We considered measures with significant correlations for a multiple regression model. Results: We found that the postoperative gait and FoG outcomes were associated with the preoperative levodopa response of clinical and kinematic gait measures. In particular, preoperative levodopa sensitivity of FoG showed high correlation with a favorable quantitative FoG outcome. Among kinematic measures, preoperative levodopa response of stride length and range of motion showed high correlation with favorable FoG outcome. In addition, the preoperative levodopa sensitivity of FoG predicted postoperative FoG outcome with high accuracy (R2=0.952; 95% confidence interval: 0.95-1.29; P<0.001). Conclusions: Preoperative clinical and kinematic measures correlated with favorable postoperative gait and FoG outcomes. The findings should be reproduced in larger and independent cohorts to verify to their predictive value.